2021
DOI: 10.3390/cells10020344
|View full text |Cite
|
Sign up to set email alerts
|

Gel-Free 3D Tumoroids with Stem Cell Properties Modeling Drug Resistance to Cisplatin and Imatinib in Metastatic Colorectal Cancer

Abstract: Researchers have developed several three-dimensional (3D) culture systems, including spheroids, organoids, and tumoroids with increased properties of cancer stem cells (CSCs), also called cancer-initiating cells (CICs). Drug resistance is a crucial issue involving recurrence in cancer patients. Many studies on anti-cancer drugs have been reported using 2D culture systems, whereas 3D cultured tumoroids have many advantages for assessing drug sensitivity and resistance. Here, we aimed to investigate whether Cisp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…Cisplatin concentrations leading to 50% inhibition of cultures’ growth in the collagen hydrogel differed by an order of magnitude (about 8 μM for SKOV3.ip-kat, and more than 80 μM for A431-GFP). Our data on the increased resistance of tumor cells cultured in 3D in vitro models compared to monolayer are in line with the results of other studies [ 54 , 55 , 56 ]. Such stability may be caused by interaction of extracellular matrix molecules with cell surface receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Cisplatin concentrations leading to 50% inhibition of cultures’ growth in the collagen hydrogel differed by an order of magnitude (about 8 μM for SKOV3.ip-kat, and more than 80 μM for A431-GFP). Our data on the increased resistance of tumor cells cultured in 3D in vitro models compared to monolayer are in line with the results of other studies [ 54 , 55 , 56 ]. Such stability may be caused by interaction of extracellular matrix molecules with cell surface receptors.…”
Section: Discussionsupporting
confidence: 92%
“…LuM-1 is a highly aggressive and non-immunogenic subclone of colon 26 48 , and metformin alone did not show significant anti-tumor effects on sc tumors or lung metastases. However, synergistic effects of RT and metformin were observed.…”
Section: Discussionmentioning
confidence: 92%
“…As for the validation data set, we next confirmed whether the significant DEGs in PDSs shared with the stroma isolated from other cancer. It has been shown that oral cancer and colorectal cancer (CRC) have a common gene expression profile and therapeutic target (29,30). Therefore, we additionally analyzed the publicly available expression profile of PDS of CRC, for which the isolation method of stromal cells was used similar to our method.…”
Section: Cellular Chemotaxis Factor Ccl2 Is Highly Expressed In Patient-derived Stromal Cellsmentioning
confidence: 99%